Gifted students' skill in solving mathematics problems: A study used gender and ethnicity as differentiating factors in senior high school - Dana Arif Lukmana (SAINTIS Publishing, 2022)
This study investigated the skills of math gifted students in high school to solve math problems. Specifically, the researcher took two factors: gender and ethnicity, as differentiators. This study involved 36 mathematically gifted students from three different schools who were randomly se-lected from 48 gifted students who were identified. The two data collection instruments used were mathematical problems (Number Theory, Algebra, and Geometry) and questionnaires, which were organized by referring to Lester's problem-solving stages. The results of the two-way ANO-VA test revealed that the average math problem skill score was 50% of the maximum score (rela-tively low). Another important finding, statistically, there is no difference in math problem skill scores based on either ethnicity or gender. This study implicitly shows that mathematically gifted students in problem-solving processes were not correlated with ethnicity or gender.